2015
DOI: 10.1007/s11606-015-3394-3
|View full text |Cite
|
Sign up to set email alerts
|

Overdose Education and Naloxone for Patients Prescribed Opioids in Primary Care: A Qualitative Study of Primary Care Staff

Abstract: BACKGROUND:The rate of fatal unintentional pharmaceutical opioid poisonings has increased substantially since the late 1990s. Naloxone is an effective opioid antidote that can be prescribed to patients for bystander use in the event of an overdose. Primary care clinics represent settings in which large populations of patients prescribed opioids could be reached for overdose education and naloxone prescription. OBJECTIVE: Our aim was to investigate the knowledge, attitudes and beliefs about overdose education a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
139
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 110 publications
(144 citation statements)
references
References 34 publications
(28 reference statements)
5
139
0
Order By: Relevance
“…Several barriers identified by participants in our study correspond with previously identified provider barriers, 14 such as the prohibitive cost of naloxone and potentially stigmatizing aspects of naloxone. While providers expressed concern that prescribing naloxone may be considered stigmatizing, 14 patient participants suggested that naloxone could be prescribed using a patient-centered approach that is empowering and non-judgmental.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Several barriers identified by participants in our study correspond with previously identified provider barriers, 14 such as the prohibitive cost of naloxone and potentially stigmatizing aspects of naloxone. While providers expressed concern that prescribing naloxone may be considered stigmatizing, 14 patient participants suggested that naloxone could be prescribed using a patient-centered approach that is empowering and non-judgmental.…”
Section: Discussionsupporting
confidence: 80%
“…Using the theoretical models that informed our interview guide content and our prior findings, we created an a priori template of codes. 14,20 Using this template as a guide, two analysts (S.K. and S.M.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…US primary care providers described insufficient time during patient appointments and inability to follow up with patients as main organizational barriers to THN (Binswanger et al, 2015). Canadian primary care providers considered existing naloxone guidelines inadequate and identified the lack of user-friendly naloxone devices, sufficient funding and training as central barriers to THN provision (Leece et al, 2015).…”
Section: Primary Carementioning
confidence: 99%
“…4 In their qualitative study of focus groups involving 56 providers discussing naloxone rescue kits, Biswinger found several important themes. 5 First, providers are not prepared or trained to help their patients understand how and when to use naloxone, or even to identify patients at risk. Second, there are logistical barriers such as how and whom to train in naloxone rescue use, since the patient is likely to be incapacitated.…”
mentioning
confidence: 99%